Exploring the innovation landscape of ginger: Insights from patent documentation analysis - Maima Matin; Bhupinder Kapoor; Monica Gulati; Michel-Edwar Mickael; Farhan Bin Matin; Agnieszka Kamińska; Joanna Bensz; Dariusz Sołdacki; Agnieszka Wierzbicka; Monika Marcinkowska-Lesiak; Ahmed Fatimi; Hong-Yan Liu; et al. (Current Research in Biotechnology)
Zingiber officinale, commonly known as ginger, holds a prominent place in both culinary and medicinal practices worldwide. This study is the first to present a comprehensive analysis of ginger-related patents, aiming to elucidate patterns and trends in innovation surrounding this versatile plant. The analysis, conducted using The Lens database, encompasses 7193 patent documents retrieved on April 26, 2025. Annual patent counts illustrate a significant increase in ginger-related patents over the years, with a notable rise observed since 2010. Analysis of the Cooperative Patent Classification system provides a structured framework for organizing these patents, revealing predominant covered categories such as food compositions, plant extracts, and tea substitutes. Additionally, the top-cited patents underscore the diverse applications of ginger, ranging from therapeutic formulations to food and beverage additives. Furthermore, examination of frequently mentioned diseases in ginger patents identifies respiratory ailments, digestive disorders, and skin conditions as key therapeutic areas. These findings show the multifaceted nature of ginger’s pharmacological properties and its potential in addressing various health challenges. Overall, by focusing on ginger as a key food and medicine plant, this study highlights the significance of patent analysis in understanding the innovation landscape of medicinal plants and nutraceuticals, and is specifically opening the ways for future research and development in ginger utilization for global health promotion and sustainable development.